Rancang Bangun Sistem Informasi Praktik Kerja Lapangan berbasis Web (Studi Kasus: Program Studi Teknik Informatika Universitas Brawijaya) - M Satria Putra Utama; Denny Sagita Rusdianto; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Field Work Practice is a subject that must be taken by every student of the Faculty of Computer Science, Universitas Brawijaya. The purpose of street vendors is to train students' ability to recognize real problems in the community and provide solutions based on the knowledge obtained while on campus. Students who want to do street vendors often have difficulty determining the location where to carry out street vendors. Students usually get references from the previous generation and also look for their own street vendors. This becomes an obstacle in terms of time and distance, as well as information about the company. Therefore, it underlies this research to implement a system of supporting student street vendor placement decisions. The development of this system uses the waterfall model method. This system implements the web with the Codeigniter framework, because the web has several advantages, namely easier access to information and can run on different platforms. The main features of this system are adding information data, adding agency data, approving student placements, seeing the value of practice and monitoring student street vendors. System testing uses the White box method for testing and integration units as well as the Black box method for testing validation. Usability testing is done using the System Usability Scale (SUS) method. The results obtained are 100% valid in functional testing and non-functional testing in the form of usability testing, based on the interpretation of SUS scores, the system is categorized as appropriate to the needs of user.